2020
DOI: 10.1038/s41598-020-67180-6
|View full text |Cite
|
Sign up to set email alerts
|

Different distribution of malaria parasite in left and right extremities of vertebrate hosts translates into differences in parasite transmission

Abstract: Malaria, a vector-borne disease caused by Plasmodium spp., remains a major global cause of mortality. Optimization of disease control strategies requires a thorough understanding of the processes underlying parasite transmission. While the number of transmissible stages (gametocytes) of Plasmodium in blood is frequently used as an indicator of host-to-mosquito transmission potential, this relationship is not always clear. Significant effort has been made in developing molecular tools that improve gametocyte de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The amount of parasite ingested by the vector during their infestation (usually a blood meal) can also generate infection heterogeneity (e.g., [31,32]). Indeed, parasite numbers vary between vertebrate hosts and also spatiotemporally within individuals [33,34]. Although a positive correlation is expected between the quantity of parasite present in the vertebrate host blood and the density of transmissible stages of the parasite found in vectors (after the incubation period), the relationship is not always obvious.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of parasite ingested by the vector during their infestation (usually a blood meal) can also generate infection heterogeneity (e.g., [31,32]). Indeed, parasite numbers vary between vertebrate hosts and also spatiotemporally within individuals [33,34]. Although a positive correlation is expected between the quantity of parasite present in the vertebrate host blood and the density of transmissible stages of the parasite found in vectors (after the incubation period), the relationship is not always obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial aggregation of gametocytes in vertebrate blood could be partially responsible for the aggregated distribution of oocysts in mosquitoes. Recent work has shown that gametocyte density can change by more than 0.4-fold between blood collected from different human body parts ([ 37 ], but see [ 38 ]). Although the direct connection between spatial heterogeneity in vertebrate blood and overdispersion in mosquitoes has never been made, it has been reported that Plasmodium gametocytes show an aggregated distribution within mosquitoes that recently fed on a human host [ 39 ].…”
Section: Introductionmentioning
confidence: 99%